Analysis of sectorial plates normally loaded over circular domains. II - Wadie A. Bassali (International Journal of Mathematics and Mathematical Sciences)
The method of images is applied to derive exact expressions for the deflections of unlimited wedge-shaped plates the central parts of which are cut, when the plate is simply supported on the radial edges, elastically restrained or free along the circular edge and is acted upon by one of three types of normal loading distributed over the surface of a circular domain. Formulae for the bending and twisting moments along the circular edge are given. Limiting forms of the obtained solutions are considered.